Komunitas Makrozoobentos Sebagai Bioindikator Kualitas Perairan Kecamatan Pantai Labu Kabupaten Deli Serdang (Macrozoobenthos Community As Bioindicator of Water Pollution in Pantai Labu Subdistrict Deli Serdang Regency) - Atikah Asry; Yunasfi Djayus; Zulham Apandy Harahap (AQUACOASTMARINE, 2014)
Pantai Labu is a coastal area which has been developing their utilization by various human activities which affect the water quality. The study of the water quality can be known by biological analysis such as macrozoobenthos. The research includes retrieval and identification of macrozoobenthos and measurements of water physical-chemical parameters. The results showed that in Kecamatan Pantai Labu waters, there are 5 classes of macrozoobenthos that consisting of 37 species. The first station has a diversity of macrozoobenthos, that is moderate, the second station and the third station have a low diversity. The community analysis stated that the every station has no resemblance species inter point. Through pollution index that the first station and the second station are classified in mild blackened condition, while the third station is classified in good condition because it has an IP value of 0.06. Macrozoobenthos as bioindicators at first station are Corbicula javanica, Thiara scabra and Pheretima sp. for mild blackened waters, at second station is Littorina sundaica, whereas the third station is Mactra fragilis and Planaria sp. which indicates good water quality.Keywords : Pantai Labu, Macrozoobenthos Community, Coastal